In‐Volume Laser Direct Writing of Silicon—Challenges and Opportunities (Laser Photonics Rev. 15(11)/2021). Issue 11 (10th November 2021) - Chambonneau, Maxime; Grojo, David; Tokel, Onur; Ilday, Fatih Ömer; Tzortzakis, Stelios; Nolte, Stefan
Abstract : Laser Direct Writing The development of in‐volume laser direct writing of silicon as it exists for transparent materials for a quarter of a century remains a major challenge to tackle. In article number 2100140, Maxime Chambonneau and co‐workers give a comprehensive review on the physical limitations to the excitation of bulk silicon with ultrashort laser pulses, the devised solutions, and the demonstrated applications.